Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer:
x = 6
Step-by-step explanation:
Step 1. Rewrite in the form of y=mx+b
Step 2. Set y = 0 and solve for x
y - 6 = x - 12
y = x - 12 + 6
y = x - 6
0 = x - 6
6 = x
BRAINLIEST please if this helped!
Answer:
y = x - 6
x = y + 6
Step-by-step explanation:
For y:
y - 6 = x - 12
y = x - 12 + 6
y = x - 6
For x:
y - 6 = x - 12
y - 6 + 12 = x
y + 6 = x
_______
Hope it helps ⚜
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.